Making 'sense' of equality in access to medicines: an ethical approach (2016)
This theoretical review outlines certain elements for discussion on the role society should play towards global and equal access to medicines. For this purpose, mention is made of the most significant theories proposed on poverty and ethics. In order to consolidate the bases for further studies on this issue, attention is paid to the reflections and contributions of the authors mentioned in this article to discuss access to medicines as a priority public policy for the bridging of a significant poverty gap, and to rethink the ethical role of scientific progress in pharmaceutical field.